2020
DOI: 10.1016/j.mimet.2020.106057
|View full text |Cite
|
Sign up to set email alerts
|

A rapid screening method for the detection of specialised metabolites from bacteria: Induction and suppression of metabolites from Burkholderia species

Abstract: Screening microbial cultures for specialised metabolites is essential for the discovery of new biologically active compounds. A novel, cost-effective and rapid screening method is described for extracting specialised metabolites from bacteria grown on agar plates, coupled with HPLC for basic identification of known and potentially novel metabolites. The method allows the screening of culture collections to identify optimal production strains and metabolite induction conditions. The protocol was optimised on tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…HPLC analysis was used to quantify and identify known B. gladioli metabolites as follows. Specialized metabolites were produced by growing on BSM-G medium (as above) and extracted directly from a 20 mm agar disc cut from the plates as described elsewhere [ 44 ]. Extracts (20 µl injection volume) were analysed on a Waters AutoPurification HPLC System fitted with a reverse-phase analytical column (Waters XSelect CSH C18, 4.6×100 mm, 5 µm) and a C18 SecurityGuard cartridge (Phenomenex) in series.…”
Section: Methodsmentioning
confidence: 99%
“…HPLC analysis was used to quantify and identify known B. gladioli metabolites as follows. Specialized metabolites were produced by growing on BSM-G medium (as above) and extracted directly from a 20 mm agar disc cut from the plates as described elsewhere [ 44 ]. Extracts (20 µl injection volume) were analysed on a Waters AutoPurification HPLC System fitted with a reverse-phase analytical column (Waters XSelect CSH C18, 4.6×100 mm, 5 µm) and a C18 SecurityGuard cartridge (Phenomenex) in series.…”
Section: Methodsmentioning
confidence: 99%
“…We then reconstructed the phylogeny of the 22 bacterial species based on these 763 single-copy core genes, and the results showed that CGB10 was closest to B. gladioli, and together they clustered with B. glumae (Figure 1A). We further confirmed the taxonomic status of CGB10 by calculating the average nucleotide identity (ANI) [28] based on the whole genome of the CGB10 strain in comparison with another six B. gladioli strains, including established rice pathogen BSR3 [24], strains isolated from healthy plants and displaying antifungal activity [29][30][31], and strains isolated from a cystic fibrosis patient [32], as well as a B. glume strain BGR1 [24], which is also known as a rice pathogen (information of selected strains was detailed in Table 1). The identity between CGB10 and the six selected B. gladioli strains was all higher than 98%, yet the identity between CGB10 and the B. glumae strain BGR1 was 88.12%.…”
Section: Genome Sequencing and Phylogenetic Analysis Of Cgb10mentioning
confidence: 62%
“…The B . ambifaria BCC1105 and P. phytofirmans PsJN hosts containing the cloned cepacin and caryoynecin BGCs also gained new antagonistic activity against S. aureus (Figure 2C ), a bacterium specifically susceptible to polyynes (Webster et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…20 mm discs were excised from each agar plate and metabolites were extracted from the agar piece by incubation in 0.5 ml extraction solvent for 2 h with gentle shaking. Ethyl acetate (EtOAc) was used for the extraction of cepacin, whilst dichloromethane (DCM) was used for caryoynencin (Webster et al, 2020 ). HPLC analysis was conducted as previously described (Webster et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation